Comparison between conventional and comprehensive sequencing approaches for genetic diagnosis of Alport syndrome. Issue 9 (30th July 2019) - Yamamura, Tomohiko; Nozu, Kandai; Minamikawa, Shogo; Horinouchi, Tomoko; Sakakibara, Nana; Nagano, China; Aoto, Yuya; Ishiko, Shinya; Nakanishi, Koichi; Shima, Yuko; Nagase, Hiroaki; Rossanti, Rini; et al.
Abstract: Background: Alport syndrome (AS) is a hereditary disease caused by mutations in COL4A3‐5 genes. Recently, comprehensive genetic analysis has become the first‐line diagnostic tool for AS. However, no reports comparing mutation identification rates between conventional sequencing and comprehensive screening have been published. Methods: In this study, 441 patients clinically suspected of having AS were divided into two groups and compared. The initial mutational analysis method involved targeted exome sequencing using next‐generation sequencing (NGS) ( n = 147, NGS group) or Sanger sequencing for COL4A3/COL4A4/COL4A5 ( n = 294, Sanger group). Results: In the NGS group, 126 patients (86%) were diagnosed with AS by NGS, while two had pathogenic mutations in other genes, NPHS1 and EYA1 . Further, 239 patients (81%) were diagnosed with AS by initial analysis in the Sanger group. Thirteen patients who were negative for mutation detection in the Sanger group were analyzed by NGS; three were diagnosed with AS. Two had mutations in CLCN5 or LAMB2 . The final variant detection rate was 90%. Discussion: Our results reveal that Sanger sequencing and targeted exome sequencing have high diagnostic ability. NGS also has the advantage of detecting other inherited kidney diseases and pathogenic mutations missed by Sanger sequencing. Abstract : Our results reveal that both Sanger sequencing and targeted exome sequencing have high diagnostic ability. Next‐generation sequencing also has the advantage of detecting other inherited kidney diseases and pathogenic mutations overlooked by Sanger sequencing.